FDZ Data description: Real-Estate Data for Germany Campus Files (RWI-GEO-RED Panel and RWI-GEO-RED Cross-Section)- Version V3.1: Advertisements on the Internet Platform lmmobilienScout24 for teaching purposes - Sandra Schaffner; Patrick Thiel (RWI - Leibniz-Institut für Wirtschaftsforschung, 2022)
The FDZ Ruhr provides two campus files on real estate advertisements in Germany: The Panel Campus File (RWI-GEO-RED Panel) and a Cross-Sectional Campus file (RWI-GEO-RED Cross-Section). The datasets are extractions of the Scientific Use Files of RWI-GEO-RED. The Panel File covers the 15 biggest cities in Germany over the whole time period whereas the Cross-Section File covers all Germany within one year (2021). The RWI-GEO-RED data are based on information from the internet platform ImmobilienScout24 and cover residential advertisements only. The campus files include apartments for sale and for rent and houses for sale. The data are available for lectures, tutorials, seminar thesis, bachelor and master thesis and scientific research. The provided dataset covers detailed regional information and a rich set of housing characteristics. Both datasets are a sample drawn and not the comprehensive data base like the Scientific Use File. The already implemented data cleaning eases the data work for students. This data report gives a brief overview of the data as well as its limitations and specifics. The data report is addressed to (potential) users of the data as support for their data preparation. The data report refers to V3.1 of both data sets.
Keywords: 330